Ketahanan Pangan Rumah Tangga Petani (Studi Empiris pada Agroekosistem Lahan Kering di Kabupaten Situbondo) - Irzaq Galuh Pranata; Mohammad Rondhi (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Dryland areas face water scarcity for crop and livestock production, as well as soils that tend to be less fertile. In turn, this results in elevated levels of food insecurity. Local governments have instituted numerous programs to increase the income of dryland farmers' households, with the expectation that this will facilitate access to food. Nevertheless, the extent of these programs' impact, including their potential to enhance the food security of dryland farmers' households, has not been thoroughly investigated. Based on indicators of food availability, access, and utilization, this investigation aims to assess the food security of dryland farmer households. In this context, cultivators' income affects households' access to food. Sopet Village was deliberately selected as the research location because it is one of the villages with the largest dryland area in the Situbondo District. This study uses a quantitative approach with a total sample of 68 farmers selected randomly using the Slovin formula. The research instrument used is a structured interview. The research method for measuring food security includes an analysis of staple food availability, a composite index analysis, and an analysis of energy and protein sufficiency levels. According to the study's findings, dryland farmer households have limited access to staple foods such as rice. This condition is caused by the low food input from rice in dryland farmer households, namely production and purchases. Dryland farmer households have high levels of food access. The proximity to markets and the high income necessary to obtain food are both indicative of the high value of food availability. Food utilization in dryland farmer households is classified as moderate deficit. Factors contributing to low food consumption may include insufficient information about nutritious, balanced diets.